Before and after the ban: energy drink consumption among physically active Polish youth - Granda, Dominika; Malczewska-Lenczowska, Jadwiga; Surała, Olga; Szczepańska, Beata (Biology of Sport, 2025)
On January 1, 2024, a nationwide ban on sales of energy drinks (EDs) to individuals under 18 came into effect in Poland. The aim of this study was to compare ED consumption, motives, and contexts of use before and after implementation of the sales ban. Two studies with similar methodology were conducted in independent samples: the first in 2022 (n = 1530, adolescents participating in extracurricular sports activities, aged 10–14 years) and the second in 2025 (n = 1083, adolescents from Handball Training Centres, aged 11–15 years). Both studies were anonymous, included participants from all provinces and applied the computerassisted web interview method. The prevalence of ED consumption among adolescents decreased significantly from 46.4% in 2022 to 19.1% in 2025 following implementation of the sales ban for minors (p < 0.001; OR = 0.27, 95%CI: 0.23–0.33). Before and after the ban, the percentage of ED consumers increased with age. Taste and consuming EDs with friends were the most frequently cited motives and circumstances in both studies. The significant decline in the proportion of ED consumers suggests that the implemented policy may have been effective, albeit to a limited extent. The ban did not alter the circumstances and motives for consumption. To our knowledge, this is the first study to directly compare ED consumption before and after implementation of such a policy among physically active adolescents. Research on a representative youth sample, including adolescents who do not train, is needed to assess the scale of the problem and the effectiveness of the sales ban.